Pathophysiological Mapping of Experimental Heart Failure: Left and Right Ventricular Remodeling in Transverse Aortic Constriction Is Temporally, Kinetically and Structurally Distinct - Platt, Mathew J.; Huber, Jason S.; Romanova, Nadya; Brunt, Keith R.; Simpson, Jeremy A. (Frontiers in Physiology, 2018)
A growing proportion of heart failure patients present with impairments in both ventricles. Experimental pressure-overload (i.e., transverse aortic constriction, TAC) induces left ventricle (LV) hypertrophy and failure, as well as right ventricle (RV) dysfunction. However, little is known about the coordinated progression of biventricular dysfunction that occurs in TAC. Here we investigated the time course of systolic and diastolic function in both the LV and RV concurrently to improve our understanding of the chronology of events in TAC. Hemodynamic, histological, and morphometric assessments were obtained from the LV and RV at 2, 4, 9 and 18wks post-surgery. Results: Systolic pressures peaked in both ventricles at 4wks, thereafter steadily declining in the LV, while remaining elevated in the RV. The LV and RV followed different structural and functional timelines, proving the patterns in one ventricle are independent from the opposing ventricle. RV hypertrophy/fibrosis and pulmonary arterial remodeling confirmed a progressive right-sided pathology. Temporality further identified both compensation and decompensation in the LV with persistent concentric hypertrophy in both phases. And finally, diastolic impairments in both ventricles manifested as an intricate progression of multiple parameters that were not in agreement until overt systolic failure was evident. Conclusions: We establish pulmonary hypertension was secondary to LV dysfunction, confirming TAC is a model of type II pulmonary hypertension. This study also challenges some common assumptions in experimental HF (e.g., the relationship between fibrosis and filling pressure) while addressing a knowledge gap with respect to temporality of RV remodeling in pressure-overload.